2018
DOI: 10.26603/ijspt20180963
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Contact and Contact Time-Loss Lower Quadrant Injury Rates in Male Collegiate Basketball Players: A Preliminary Report

Abstract: Background: Male collegiate basketball (BB) players are at risk for musculoskeletal injury. The rate of time-loss injury in men's collegiate BB, for all levels of National Collegiate Athletic Association (NCAA) competition, ranges from 2.8 to 4.3 per 1000 athletic exposures (AE) during practices and 4.56 to 9.9 per 1000 AE during games. The aforementioned injury rates provide valuable information for sports medicine professionals and coaching staffs. However, many of the aforementioned studies do not provide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This was corroborated by a recent systematic review showing that nine out 11 selected studies (3257 participants; age: 18–65) reported no association between lower body power and musculoskeletal injuries 54 . Two other studies involving 71 collegiate basketball players (age 20.2 ± 1.9 years) and 127 Swedish soccer players (aged 16–36) both failed to establish an association between lower extremity power and sports injuries as well 55,56 …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This was corroborated by a recent systematic review showing that nine out 11 selected studies (3257 participants; age: 18–65) reported no association between lower body power and musculoskeletal injuries 54 . Two other studies involving 71 collegiate basketball players (age 20.2 ± 1.9 years) and 127 Swedish soccer players (aged 16–36) both failed to establish an association between lower extremity power and sports injuries as well 55,56 …”
Section: Discussionmentioning
confidence: 70%
“…54 Two other studies involving 71 collegiate basketball players (age 20.2 ± 1.9 years) and 127 Swedish soccer players (aged 16-36) both failed to establish an association between lower extremity power and sports injuries as well. 55,56…”
Section: Comparison With Other Studiesmentioning
confidence: 99%